(untitled) (Global Journal of Management and Business Research, 2022)
This paper aims to propose a model for predicting SME insolvency in the Sub-Saharan context. Based on a sample of 1183 Cameroonian SMEs from 2013 to 2015, we performed a logistic regression in panel data. The results show a persistence of insolvency over time when effected in an SME. It is also seen in the results that SME insolvency is determined by financial variables related to business management, financial structure, and profitability. On the other hand, it is determined by non-financial variables such as management quality, staff compensation, and SME size, which reinforce the power of insolvency prediction models. However, some determinants of insolvency in small firms are insignificant in medium-sized firms.